Critical Role of Irrigation Efficiency for Cropland Expansion in Western China Arid Agroecosystems. Issue 9 (19th September 2022) - Fu, Jianyu; Wang, Weiguang; Zaitchik, Benjamin; Nie, Wanshu; Fei, Esther Xu; Miller, Scot M.; Harman, Ciaran J.
Abstract: The rapid expansion of desert croplands in the Tarim River Basin, which depend heavily on irrigation with meltwater, has coincided with increases in snow and glacier melt in the high mountains of Asia during the past decades. Meanwhile, there have been intensive investments in modern irrigation technology aimed at enhancing water use efficiency. The importance of meltwater in mountain front agroecosystems has been widely acknowledged, but it is not clear how important this meltwater versus increased irrigation efficiency (IRE) has been for the rapid cropland expansion in the Tarim River Basin. Here we investigate changes in water supply and demand of the meltwater‐irrigated cropland bordering the Taklamakan Desert based on multiple remotely sensed and ground‐based observation datasets, and we evaluate the contributions of improved IRE to cropland expansion. We find that cropland has increased by 58% between 1990 and 2015. Net streamflow to the region increased by +10% over the same period, but the rate of increase was slower after 2000. This deceleration contrasts with the growing irrigation demand (IRD) imposed by dramatic cropland expansion. At the same time, IRE increased by 73% from 1990 to 2015, providing 18.5 billion m 3 irrigation water savings, which offset the increased IRD. With the adoption of more efficient irrigation, crop water stress due to continuous agricultural expansion in the Tarim River Basin declined significantly, making the dependence of agricultural production on runoff from glacier and snow meltwater less than would otherwise be expected. Plain Language Summary: The rapid expansion of irrigated cropland in the desert hinterland of the Tarim River Basin has coincided with increases in meltwater and efforts to improve irrigation efficiency (IRE). We conducted comprehensive assessments of whether water resources derived from increased meltwater can satisfy the rising irrigation demand, and the relative contributions of increased runoff and enhanced IRE to cropland expansion. Our results suggest that the increased water availability from meltwater cannot meet the requirement of continuous cropland expansion from 1990 to 2015, but the substantial improvement in IRE over the same period provided effective compensation from the demand‐side. These findings underscore the value of technological investments for enhancing the resilience of agriculture to long‐term changes in meltwater related to climate change. Key Points: The relative contributions of increased streamflow and enhanced irrigation efficiency to cropland water use were explored The dependence of agricultural production on increased glacier and snow meltwater was reduced by improving irrigation efficiency High irrigation efficiency could provide short‐term resilience to water scarcity under climate change